Promoting social partnership in employee training - Czech Republic country report - Zibrowius, Michael (Brussels, 2018)
"Joint Recommendations addressing social partnership in employee training were adopted during a conference held on 19 June 2018 in Brussels. A report was also presented during the conference. The recommendations and report were developed following the consultation of national members in order to develop country reports which outlined employee training in the 12 target countries (AT, CZ, DE, DK, ES, EE, FR, IE, NL, PL, PT, SE). These country reports also formed the bases of discussions during the three decentralised seminars."